ANALISIS PENGARUH DIAMETER PIPA SUCTION PADA POMPA PANASONIC DEEP WELL PUMP TERHADAP KAPASITAS POMPA - Dedy Rachman Ardian; Sutrisno; Aji Suherman (Wahana Teknik, 2022)
The purpose of this study was to determine the value of the pump capacity at each suction pipe replacement and to determine the power value caused by the effect of replacing the suction pipe. In this research, there are several stages starting with the installation of a pump, measuring the flow of water, measuring the voltage and measuring the current of the water pump. Fluid flow rate is the volume rate or the volume of fluid flowing per unit time. How to measure the power of a single phase electric motor, which requires a tool called a clammeter where this tool can be used to measure the value of current and voltage. From the results of measuring the current and voltage values, the formula P = V x I, P = motor power value, V = voltage value and I = current value. The results showed that the maximum pump work on the replacement of the suction pipe with a size of 2 ½ inches with a power value of 212,2 watts, a pump capacity flow rate of 0,135 liters/second and a friction head of 0,000057368